Qualitative Research A Field Manual for Ministry Students - Lincoln, Timothy (Atla Open Press, 2021)
Qualitative research helps investigators better understand the experiences of others. Qualitative Research: A Field Manual for Ministry Students assumes no prior background in research involving human subjects. The examples and exercises in this book are drawn from variety of ministry settings and religious communities. The book addresses the distinctive features of final projects in Doctor of Ministry programs, including how to evaluate a project's success. Some research methods textbooks discuss theory in depth but provide little explanation about how to conduct a study. This book explains how to use specific techniques and procedures, from study design and recruitment of participants to collection of data, analysis (coding), and interpretation of findings. Included is a databank containing transcribed interviews from qualitative studies. These data can be used to practice the analysis techniques discussed in the book.